Self-esteem in sexual minority young adults: a qualitative interview study exploring protective factors and helpful coping responses. (19th May 2022) - Bridge, Livia; Smith, Patrick; Rimes, Katharine A.
Abstract: Research on mental health inequalities between sexual minority and heterosexual young adults has historically focussed on the additional stress processes that might explain this disparity. However, more recently there has been a shift towards research focussed on resilience factors that might promote mental health in sexual minority young adults. Self-esteem is one such proposed resilience factor. This study aimed to explore the factors that promote or protect self-esteem itself in sexual minority young adults. A semi-structured interview study was conducted with 20 sexual minority young adults (aged 16–24) to explore their perspectives on the factors, responses and strategies that have helped to protect or promote their self-esteem. Six themes were identified from thematic analysis: helpful responses to minority stress; sexuality acceptance; positive LGBTQ + social connections and representations; positive social relationships and evaluation; successes and positive qualities and general coping strategies for low self-esteem. Findings are discussed in terms of their theoretical implications.